International Legal Challenges in Addressing Diplomatic Defection Involving a Third State: A Normative Study of the Ri Il Kyu Case - Marcello Ardra P. S; Dhiana Puspitawati; Adi Kusumaningrum (IJBLE Scientific Publications Community Inc., 2026)
Diplomatic relations remain one of the oldest and most institutionalised mechanisms through which states communicate, negotiate, protect national interests and maintain peaceful cooperation. The Vienna Convention on Diplomatic Relations 1961 (VCDR) codifies the core rules governing the establishment of diplomatic relations, the functions of diplomatic missions, diplomatic privileges and immunities, and remedial measures such as persona non grata. Yet the Convention does not expressly regulate the situation in which a diplomatic agent abandons his or her post in the receiving state and seeks protection or permanent relocation in a third state. Using a normative juridical method with statutory, conceptual and case approaches, this article examines the reported defection of Ri Il Kyu, a North Korean diplomat posted in Cuba who defected with his family to South Korea in November 2023. The article argues that the problem should not be described as a complete legal vacuum, because several applicable regimes already exist, including the VCDR, treaty law, human rights law, refugee law and peaceful dispute settlement under the United Nations Charter. However, these regimes are fragmented and do not provide an integrated procedure for allocating rights and obligations among the sending state, the receiving state and the third state. The article therefore proposes a specialised multilateral protocol or soft-law guideline on diplomatic defection, built upon good faith, proportionality, sovereign equality, non-intervention, non-refoulement, protection of family members, confidentiality of official materials and peaceful dispute settlement.